Effects of High and Low Temperature on the Tensile Strength of Glass Fiber Reinforced Polymer Composites - Kumarasamy, S.; Abidin, M. Shukur Zainol; Bakar, M. N. Abu; Nazida, M.S.; Mustafa, Z.; Anjang, A. (IOP Publishing, 2018)
In this paper, the tensile performance of glass fiber reinforced polymer (GFRP) composites at high and low temperature was experimentally evaluated. GFRP laminates were manufactured using the wet hand lay-up assisted by vacuum bag, which has resulted in average fibre volume fraction of 0.45. Using simultaneous heating/cooling and loading, glass fiber epoxy and polyester laminates were evaluated for their mechanical performance in static tensile loading. In the elevated temperature environment test, the tension mechanical properties; stress and modulus were reduced with increasing temperature from 25oC to 80oC. Results of low temperature environment from room temperature to a minimum temperature of -20oC, indicated that there is no considerable effect on the tensile strength, however a slight decrease of tensile modulus were observed on the GFRP laminates. The results obtained from the research highlight the structural survivability on tensile properties at low and high temperature of the GFRP laminates.